1958
DOI: 10.1161/01.res.6.4.424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Energy to Protein Ratio on Serum and Carcass Cholesterol Levels in Chicks

Abstract: Soft" fats were found to depress significantly serum cholesterol levels in diets of high energy to protein (E/P) ratio but not in diets of low energy to protein ratios. A low (E/P) ratio depressed serum cholesterol values, regardless of the type of fat in the diet. The E/P ratio may represent the unknown factor in the equations of workers who have tried to relate the effect of dietary fats to serum cholesterol levels.T HE effect of the energy to protein (E/P) ratio on the serum and carcass cholesterol level li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1959
1959
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 22 publications
(8 reference statements)
1
2
0
Order By: Relevance
“…In agreement with Kokatnur et al (1958), the present study found that increasing the dietary protein was more effective in reducing serum cholesterol of male chickens than decreasing the dietary fat. In agreement with Kokatnur et al (1958), the present study found that increasing the dietary protein was more effective in reducing serum cholesterol of male chickens than decreasing the dietary fat.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with Kokatnur et al (1958), the present study found that increasing the dietary protein was more effective in reducing serum cholesterol of male chickens than decreasing the dietary fat. In agreement with Kokatnur et al (1958), the present study found that increasing the dietary protein was more effective in reducing serum cholesterol of male chickens than decreasing the dietary fat.…”
Section: Discussionsupporting
confidence: 91%
“…Studies with adequately nourished chickens (Grant and Fahrenbach, 1957, 1959; Kritchevsky et al, 1958; Kokatnur et al, 1958b), rabbits (Wells, 1957; Grant and Fahrenbach, 1959; Wells and Anderson, 1959; Pollak, 1961) and rats (Portman et al, 1956; Wells, 1957; Wells and Cooper, 1958; Adams et al, 1959; Marshall et al, 1959; Nath et al, 1959; Wells et al, 1960; Guggenheim et al, 1960) demonstrate that a positive correlation exists between dietary carbohydrate and the serum cholesterol level. However, this relationship does not prevail in animals fed a cholesterol‐free diet (Grant and Fahrenbach, 1957, 1959; Guggenheim et al, 1960; Pollak, 1961).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Rats given 40 per cent sucrose diets absorbed 40.4 per cent of the dietary cholesterol and 7.5 per cent of the isotope (Wells and Cooper, 1958; Wells et al, 1960). With regard to the relationship between the quantities of carbohydrate and protein in the diet, a high energy‐protein ratio has been demonstrated to produce hypercholesterolemia in chicks (Kokatnur et al, 1958b).…”
Section: Review Of the Literaturementioning
confidence: 99%